2013
DOI: 10.1111/agec.12074
|View full text |Cite
|
Sign up to set email alerts
|

What are the farm‐level impacts of Malawi's farm input subsidy program? A critical review

Abstract: This article provides a critical analysis of the current frontier of research evaluating Malawi's Farm Input Subsidy Program (FISP), whose main objectives are increasing maize production, promoting household food security, and enhancing rural incomes. We focus on farm‐level studies in Malawi, identifying consistent and contrasting research results in order to draw important policy lessons and provide suggested avenues for future research. While national production estimates suggested dramatic increases in maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 21 publications
4
119
0
1
Order By: Relevance
“…The findings that FSPs are effective for increasing fertilizer use and boosting maize production in the short term coincide with other studies' findings (e.g., [4,53]). However, the short-term orientation of FSPs makes the maize production system in general and maize availability in particular vulnerable to changes in the government's FSP expenditure and changes in fertilizer prices.…”
Section: Resultssupporting
confidence: 90%
“…The findings that FSPs are effective for increasing fertilizer use and boosting maize production in the short term coincide with other studies' findings (e.g., [4,53]). However, the short-term orientation of FSPs makes the maize production system in general and maize availability in particular vulnerable to changes in the government's FSP expenditure and changes in fertilizer prices.…”
Section: Resultssupporting
confidence: 90%
“…Malawi had the highest rate, undoubtedly related to its large-scale Farm Input Subsidy Program (FISP). FISP, implemented since 2005/06, targets about 50 % of farmers in the country to receive subsidized fertilizer for maize production, with additional vouchers for tobacco fertilizers and free modern maize seed (Lunduka et al 2013). One study found that between 69 and 82 % of sampled farmers that received a FISP voucher for maize seed redeemed their coupon for a DT maize variety (Holden and Fisher 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Higher yields could also contribute to higher belowground soil organic matter that could contribute to other biogeochemical benefits. Lunduka et al (2013) conducted a cost-benefits analysis of subsidized fertilizer from 2005/2006to 2008. Lunduka et al (2013 concluded that the incentive programs of maize fertilizer subsidies were not very effective at increasing yields and food security.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one of their recommendations was that the programs be improved in such a way to increase timely application of fertilizer, since the distribution of the product may not occur when the fertilizer is needed. Lunduka et al (2013) shows that increasing food security is not just a scientific question as far as determining the soil and physical factors, but that there is also a human dimension and social aspects that are very important for food security as well as the effectiveness of subsidized programs. These are examples of how the human dimension of conservation is an important aspect to consider in climate change adaptation efforts and examples of how management decisions (Lal et al 2011) and conservation practices (Delgado et al 2011) are important factors in adapting to climate change.…”
Section: Resultsmentioning
confidence: 99%